The Position of Deaf Witnesses in Proving Divorce (Syiqaq) Cases in Religious Courts - handoko, riki; Pagar, Pagar; Tanjung, Dhiauddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Abstract                                                                          Based on article 22 of PP Number 9 of 1975, article 76 of Law Number 7 of 1989 and article 134 of Presidential Instruction Number 1 of 1991, Divorce (syiqaq) where disputes and quarrels are continuous must be proven by witness testimony, so The position of the witness is an important thing in deciding a divorce case. Witnesses who are present in court must materially see, hear and experience directly the legal events that occur, this must be in accordance with article 172 HIR/308 Rbg in conjunction with article 76 Law Number 7 of 1989. Meanwhile, in Islamic law, the position of deaf witnesses is that the majority of ulama seemed to have absolutely no tolerance for their opportunity to be witnesses. They agreed that hearing what the parties said and understanding what they meant was an absolute requirement for witnesses. The argument is because something that is the object of the witness is words. Law No.19/2011 about concerning ratification of the CRPD and the principle of Equality Before the Law also states the same thing, which does not differentiate between people in person. trial, while formally a deaf witness is not a mentally disabled witness, he just lacks hearing but can see and judge events well._________________________